The Effect of Acidifier-Dextrose against Hen Day Production and Feed Conversion Ratio in Laying Hens Infected with Avian Pathogenic Escherichia coli - Sunaryo Hadi Warsito; Emy Koestanti Sabdoningrum; Nana Tripalupi; Ayu Nur Hidayati; Anwar Ma’ruf; Poedji Hastutiek; Mirni Lamid; M. Anam Al-Arif; Herry Agoes Hermadi; Oky Setyo Widodo (Veterinary Medicine International)
Colibacillosis in Indonesia until now still appears frequently, so the case of colibacillosis laying hens cannot reach the peak of egg production; the egg production period is delayed and easily infected with other diseases. The purpose of this research is that the acidifier-dextrose combination is expected to be able to suppress the development of Avian Pathogenic Escherichia coli (APEC) bacteria in laying hens so that, in the end, the case of colibacillosis can be controlled in Indonesia. A total of 240 heads of laying hens were divided into 6 treatments and each consisted of 40 replications. The results of this research state that a combination of acidifier-dextrose can increase Hen Day Production (p<0.05) and decrease Feed Conversion Ratio (p<0.05) in laying hens infected with APEC. The Hen Day Production results of the treatment group infected with APEC showed the lowest results, amounting to 65.75% whereas the other treatments are still above 90%. Furthermore, the highest Feed Conversion Ratio results were on treatments infected with APEC, which amounted to 2.17 while other treatments of the Feed Conversion Ratio results are still below 1.80. In general, the use of a combination of acidifier and dextrose with the lowest dose, that is, 1 g/3.75 liters of drinking water can still give good results to Hen Day Production and Feed Conversion Ratio for laying hens infected with APEC. Giving combination of acidifier-dextrose can increase Hen Day Production and decrease Feed Conversion Ratio in laying hens infected with APEC. The recommended dosage of acidifier-dextrose combination in laying hens based on this research is 1 g/3.75 liters of drinking water.